Answer:
She made her first error in step 3 because the sine, cosine, and tangent ratios are incorrect, which also results in incorrect cosecant, secant, and tangent functions.
Step-by-step explanation:
Francesca made her first error in step 3 because her sine, cosine, and tangent trigonometric ratio values are incorrect.
How to work with trigonometric ratios?The correct steps to use in this regards are as follows;
Step 1;
A unit circle is shown. A ray intersects point (-2, -10) in quadrant 3. θ is the angle formed by the ray and the x-axis in quadrant 1.
Step 2;
r = √[(-2)² + (-10)²] = √104 = 2√26
Step 3;
cos θ = -2/(2√26) = -1/√26 = -(√26)/26
sin θ = -10/(2√26) =-5/√26 = -5(√26)/26
tan θ = -10/-2 = 5
sec θ = 1/sin θ = 1/-(√26)/26 = -26/√26
cosec θ = 1/cos θ = 1/-5(√26)/26 = -(√26)/5
cot θ = 1/tan θ = 1/5
Thus, Francesca made her first error in step 3 because the correct sine, cosine, and tangent ratios above differ from hers which was incorrect which lead to incorrect values of cosecant, secant, and tangent functions.
Read more about trigonometric ratios at; https://brainly.com/question/15953530
After returning from a holiday to the USA, Megan has some American coins: A 25c coins and B 10c coins with a total value of $1.95, where A and B are both counting numbers. how many different values of A can Megan have?
Megan can have 7 different values of A for the number of 25c coins she possesses.
Given:
Megan has 25c coins and 10c coins with a total value of $1.95.
To find:
Number of different values of A (number of 25c coins) Megan can have.
Step-by-step solution:
Let A represent the number of 25c coins and B represent the number of 10c coins.From the given information, we can form the equation 25A + 10B = 195 (since the total value is $1.95).We know A and B are counting numbers (positive integers).Now, find the possible values of A that satisfy the equation and the conditions: A = 1, 2, 3, 4, 5, 6, 7.Therefore, Megan can have 7 different values of A for the number of 25c coins she possesses.
Find the vertex of the parabola y=2x^2+8x-9
Answer:
The vertex is (-2,-17).
Step-by-step explanation:
We have given y=2x²+8x-9
To find the x-coordinates we use:
xv= -b/2a
where a=2 and b=8
Now put the values in the formula:
xv= -(8)/2(2)
xv=-8/4
xv= -2
Now to find the y coordinates, we will simply substitute the value in the given equation:
y=2x²+8x-9
y=2(-2)²+8(-2)-9
y=2(4)-16-9
y=8-16-9
y=-8-9
y= -17
Therefore the vertex is(-2, -17)....
How do I solve this?
Answer:
2y = 3x
Step-by-step explanation:
general formula for a straight line is given as
y = mx + b
Given 2 points (2,3) and (4,6), we can use the attached formula to calculate the slope, m of the line which connects the 2 points
m = (6-3) / (4-2) = 3/2
hence the general formula becomes
y = (3/2) x + b
Substitute one of the given points into this equation to find b.
We pick point (2,3)
3 = (3/2) (2) + b
b = 0
hence the equation is
y = (3/2)x
2y = 3x (answer)
Find the sum of (-4+ i) and (10 - 51).
-3+ 51
-3-51
06-41
6-61
DONE
Answer:
The correct answer is 6-4i
Answer:
6 - 4i .
Step-by-step explanation:
I will assume that (10 - 51) is ( 10 - 5i) since the other number is a complex number.
You add the real parts and the imaginary parts separately.
(-4 + i) + (10 - 5i)
= (-4 + 10) + (i - 5i)
= 6 - 4i .
The length of a spring varies directly with the mass of an object that is attached to it. When a 30 gram object is attached the spring stretches 9 centimeters. Which equation relates the mass of and object, m, and the length of a spring s.
A s= 3/10m
B s= 10/3m
C m= 3/10s
D m=10/3s
Answer:
A. s = 3/10 m.
Step-by-step explanation:
s = km where k is a constant , s = the length of the string and m = the mass of the object.
Substituting m = 30 and s = 9:
9 = k * 30
k = 9/30 = 3/10
So the equation is s = 3/10 m.
help me to do this question friends
Answer:
First draw two axes x and y. Then mark all points for which x=4, this is a vertical line. Do the same for the other sides and you will find a square with side length 8.
Which shows the expression x^2-1/x^2-x
Answer:
[tex]\large\boxed{\dfrac{x^2-1}{x^2-x}=\dfrac{x+1}{x}=1+\dfrac{1}{x}}[/tex]
Step-by-step explanation:
[tex]\dfrac{x^2-1}{x^2-x}=\dfrac{x^2-1^2}{x(x-1)}\qquad\text{use}\ a^2-b^2=(a-b)(a+b)\\\\=\dfrac{(x-1)(x+1)}{x(x-1)}\qquad\text{cancel}\ (x-1)\\\\=\dfrac{x+1}{x}=\dfrac{x}{x}+\dfrac{1}{x}=1+\dfrac{1}{x}[/tex]
Answer:
its b on edge 2021
Step-by-step explanation:
find the perimeter of a triangle with side lengths of 16.3 CM 18.75 cm and 24.2 centimeters.
Answer:
59.25 cm
Step-by-step explanation:
The perimeter means the sum of all the sides of a figure.
The perimeter of a triangle would be sum of all 3 sides (triangle has 3 sides).
The measure oof 3 sides are given, so we just need to add them to get the perimeter.
Perimeter = 16.3 + 18.75 + 24.2 = 59.25 cm
To find the perimeter of the triangle, add the side lengths of 16.3 cm, 18.75 cm, and 24.2 cm to get a total of 59.25 cm. The formula used is simple addition of all side lengths.
To find the perimeter of a triangle, you need to add up the lengths of all its sides. The side lengths given are 16.3 cm, 18.75 cm, and 24.2 cm.
First, add the length of the first side: 16.3 cm + 18.75 cm = 35.05 cm.Second, add the length of the second side to the sum: 35.05 cm + 24.2 cm = 59.25 cm.Therefore, the perimeter of the triangle is 59.25 cm.
What is the following quotient
Answer:
√(3)/2
Step-by-step explanation:
To find the quotient, rationalize the denominator by multiplying both the numerator and denominator by √(6)
3√(8)*√(6) = 3√(48)
4√(6)*√(6) 24
Next, simplify the top radical
12√(3) = √(3)/2, This is the answer, it cannot be simplified any further.
24
For this case we must find the quotient of the following expression:
[tex]\frac {3 \sqrt {8}} {4 \sqrt {6}} =[/tex]
We combine [tex]\sqrt {6}[/tex] and [tex]\sqrt {8}[/tex] into a single radical:
[tex]\frac {3 \sqrt {\frac {8} {6}}} {4} =\\\frac {3 \sqrt {\frac {4} {3}}} {4} =\\\frac {3 \frac {\sqrt {4}} {\sqrt {3}}} {4} =\\\frac {3 \frac {2} {\sqrt {3}} * \frac {\sqrt {3}} {\sqrt {3}}} {4} =[/tex]
[tex]\frac {3 * \frac {2 \sqrt {3}} {3}} {4} =\\\frac {\frac {6 \sqrt {3}} {3}} {4} =\\\frac {6 \sqrt {3}} {12} =\\\frac {\sqrt {3}} {2}[/tex]
Answer:
[tex]\frac {\sqrt {3}} {2}[/tex]
What is the area of the sector having a radius of 8 and a central angle of 5π3
radians?
A. 320π/3 units²
B. 50π units²
C. 160π/3 units²
D. 140π/3units²
Area of a full circle is PI x r^2
Area = 3.14 x 8^2 = 200.96
Area of a sector is area * central angle / full circle
Area = 200.96 x 5PI/3 / 2PI = 160PI/3
Answer is C.
Answer:[tex]\frac{160\pi }{3} units^2[/tex]
Step-by-step explanation:
Given
Angle subtended by sector is[tex]\frac{5\pi }{3}[/tex]
radius =8 units
[tex]Area of sector=\frac{\theta }{2\pi }\pi r^2 [/tex]
[tex]A=\frac{20\times 8\pi }{3}[/tex]
[tex]A=\frac{160\pi }{3}[/tex]
Rafeal has been given a list of 5 bands and asked to place a vote. His vote must have the names of his favorite, second favorite, and third favorite bands from the list. How many different votes are possible?
Answer:
60 different votes.
Step-by-step explanation:
This is a permutations question. There are a total of 5 bands to be voted for, and Rafeal has to vote only for 3 of the bands. It is also mentioned that the voting has to be done for the favorite, the second favorite, and the third favorite bands from the list. This means that the order of selection is important. This means that permutations will be used. Thus, 3 bands out of 5 have to be selected in an order. This implies:
5P3 = 5*4*3 = 60 possibilities.
There are 60 different votes!!!
Answer: 60 different votes are possible
Step-by-step explanation:
We have a list of 5 bands and we must choose 3 of them. In this case, the order of the election is important. Therefore this is a problem that is solved using permutations.
The formula for permutations is:
[tex]nPr=\frac{n!}{(n-r)!}[/tex]
Where n is the number of bands you can choose and you choose 3 of them.
Then we calculate:
[tex]5P3 =\frac{5!}{(5-3)!}\\\\5P3=\frac{5!}{2!}\\\\5P3 = 60[/tex]
Finally, the number of possible votes is 60
9x2+4y2 = 36 The foci are located at:
Answer:
The foci are located at [tex](0,\pm \sqrt{5})[/tex]
Step-by-step explanation:
The standard equation of an ellipse with a vertical major axis is [tex]\frac{x^2}{b^2}+\frac{y^2}{a^2}=1[/tex] where [tex]a^2\:>\:b^2[/tex].
The given equation is [tex]9x^2+4y^2=36[/tex].
To obtain the standard form, we must divide through by 36.
[tex]\frac{9x^2}{36}+\frac{4y^2}{36}=\frac{36}{36}[/tex]
We simplify by canceling out the common factors to obtain;
[tex]\frac{x^2}{4} +\frac{y^2}{9}=1[/tex]
By comparing this equation to
[tex]\frac{x^2}{b^2}+\frac{y^2}{a^2}=1[/tex]
We have [tex]a^2=9,b^2=4[/tex].
To find the foci, we use the relation: [tex]a^2-b^2=c^2[/tex]
This implies that:
[tex]9-4=c^2[/tex]
[tex]c^2=5[/tex]
[tex]c=\pm\sqrt{5}[/tex]
The foci are located at [tex](0,\pm c)[/tex]
Therefore the foci are [tex](0,\pm \sqrt{5})[/tex]
Or
[tex](0,-\sqrt{5})[/tex] and [tex](0,\sqrt{5})[/tex]
Find the average rate of change of the function
f(x) = √x +1 on the interval 4 ≤ x ≤ 9. Recall that
the coordinates for the start of the interval are (4,
3).
What are the coordinates for the end of the
interval?
o (9,4)
o (9,3)
o (9, 82)
Answer:
Oops I went too far.
The other point is (9,4).
The average rate of change is 1/5.
Step-by-step explanation:
So I think your function is [tex]f(x)=\sqrt{x}+1[/tex]. Please correct me if I'm wrong.
You want to find the slope of the line going through your curve at the points (4,f(4)) and (9,f(9)).
All f(4) means is the y-coordinate that corresponds to x=4 and f(9) means the y-coordinate that corresponds to x=9.
So if [tex]f(x)=\sqrt{x}+1[/tex], then
[tex]f(4)=\sqrt{4}+1=2+1=3[/tex] and
[tex]f(9)=\sqrt{9}+1=3+1=4[/tex].
So your question now is find the slope of the line going through (4,3) and (9,4).
You can use the formula [tex]\frac{y_2-y_1}{x_2-x_1}[/tex] but I really like to just line up the points vertically and subtract then put 2nd difference over 1st difference. Like this:
( 9 , 4)
-( 4 , 3)
-------------
5 1
So the slope is 1/5.
The average rate of change of the function f on the interval [4,9] is 1/5.
A function describes the relationship between related variables.
The average rate of change of f(x) over 4 ≤ x ≤ 9 is [tex]\frac 15[/tex].The coordinates of the end interval is (9,4)Given that:
[tex]f(x) = \sqrt x + 1,\ 4 \le x \le 9[/tex]
The average rate of change (m) is calculated as:
[tex]m = \frac{f(x_2) - f(x_1)}{x_2 - x_1}[/tex]
[tex]m = \frac{f(9) - f(4)}{9 - 4}\\[/tex]
So, we have:
[tex]m = \frac{f(9) - f(4)}{5}[/tex]
Calculate f(4)
[tex]f(x) = \sqrt x + 1[/tex]
[tex]f(4) = \sqrt 4 + 1[/tex]
[tex]f(4) = 2 + 1[/tex]
[tex]f(4) = 3[/tex]
Calculate f(9)
[tex]f(x) = \sqrt x + 1[/tex]
[tex]f(9) = \sqrt 9 + 1[/tex]
[tex]f(9) = 3 + 1[/tex]
[tex]f(9) = 4[/tex]
So, we have:
[tex]m = \frac{f(9) - f(4)}{5}[/tex]
[tex]m = \frac{4 - 3}{5}[/tex]
[tex]m = \frac{1}{5}[/tex]
Recall that:
[tex]f(4) = 3[/tex] --- this represents the coordinate of the start interval
[tex]f(9) = 4[/tex] --- this represents the coordinate of the end interval
Hence, the coordinates of the end interval is (9,4)
Read more about average rates of change at:
https://brainly.com/question/23715190
Please please answer this correctly
Answer:
67.972 ÷ 10 = 6.7972
679.72 ÷ 10 = 67.972
6797.2 ÷ 10 = 679.72
6797200 ÷ 10 = 679720
Bob's age is 4 times greater than Susanne age. Dakota is three years younger than Susanne. the sum of bobs , Susanne's , and Dakota's ages is 93. what is Susanne's age
Answer:
Susanne is 16 years old.
Step-by-step explanation:
You're gonna need three equations.
Key: B = Bob, D = Dakota, s = Susanne
B = 4s
D = s - 3
B + D + s = 93
Now plug in B and D into the third equation:
4s + (s - 3) + s = 93
Now solve it:
4s + s - 3 + s = 93
6s - 3 = 93
+3 +3
6s = 96
6s/6 = 96/6
s = 16
Bob's age is 4 times greater than Susanne's age, and Dakota is 3 years younger than Susanne.
The sum of their ages is 93. Susanne's age is 16.5.
Explanation:Let's assign variables to represent the ages of the individuals involved:
Bob's age: BSusanne's age: SDakota's age: DWe are given that Bob's age is 4 times greater than Susanne's age, so we can write the equation B = 4S.
We are also told that Dakota is three years younger than Susanne, so we can write the equation D = S - 3.
The sum of their ages is given as 93, so we can write the equation B + S + D = 93.
Substituting the first equation into the second equation, we get D = 4S - 3.
Substituting the values from the second and third equations into the fourth equation, we have (4S - 3) + S + (S - 3) = 93.
Simplifying this equation, we get 6S - 6 = 93. Adding 6 to both sides, we have 6S = 99. Dividing both sides by 6, we find that S = 16.5.
Therefore, Susanne's age is 16.5.
why is .3 repeating a rational number
Answer:
.333333... can be expressed as 1/3.
Step-by-step explanation:
A rational number is defined as:
any number that can be expressed as the quotient or fraction p/q of two integers, a numerator p and a non-zero denominator q.
aka, any number that you can express as a fraction.
Any person who has spent enough time in math should be familiar with the fact that the thirds (aka 1/3, 2/3) are repeating decimals, but are rational numbers as they can be written as whole number fractions.
If you didn't know this, don't worry. You'll get it soon enough.
Hope this helped!
On an average work day, 160 cars go through a toll booth per hour.The driver of each car pays a $1.50 toll how much money is collected in toll in 8 hours
Your question asks how much money was collected at the toll for a period of 8 hours.
Answer: $1,920To find the answer, we would need to gather some important information from the question.
Important information:
160 cars go through the toll per hourEach car pays $1.50With the information above, we can solve the problem.
First, let's find how much money the toll makes in one hour. To find this, we need to multiply 1.50 by 160 cars, since the toll costs $1.50 and 160 cars go through it per hour.
[tex]1.50*160=240[/tex]
The toll makes $240 per hour.
Now, since we need to find how much the toll makes in 8 hours, we need to multiply 240 by 8.
[tex]240 * 8=1,920[/tex]
When you're done solving, you should get 1,920.
This means that the toll makes $1,920 in 8 hours.
I hope this helps!Best regards,MasterInvestorSimplify 5(x - 2) - 3x + 7.
5(x - 2) - 3x + 7.
First use the distributive property:
5(x-2) = 5x-10
Now you have:
5x - 10 - 3x +7
Now combine like terms to get:
2x - 3
Answer:
2x -3
Step-by-step explanation:
5(x - 2) - 3x + 7
Distribute the 5
5x -10 -3x+7
Combine like terms
5x-3x -10 +7
2x -3
Drag the tiles to the boxes to form correct pairs. Not all tiles will be used.
Match the function with its inverse.
File ATTACHED
THANK YOU
Answer:
Part 1) [tex]f(x)=\frac{2x-1}{x+2}[/tex] -------> [tex]f^{-1}(x)=\frac{-2x-1}{x-2}[/tex]
Part 2) [tex]f(x)=\frac{x-1}{2x+1}[/tex] -------> [tex]f^{-1}(x)=\frac{-x-1}{2x-1}[/tex]
Part 3) [tex]f(x)=\frac{2x+1}{2x-1}[/tex] -----> [tex]f^{-1}(x)=\frac{x+1}{2(x-1)}[/tex]
Part 4) [tex]f(x)=\frac{x+2}{-2x+1}[/tex] ----> [tex]f^{-1}(x)=\frac{x-2}{2x+1}[/tex]
Part 5) [tex]f(x)=\frac{x+2}{x-1}[/tex] -------> [tex]f^{-1}(x)=\frac{x+2}{x-1}[/tex]
Step-by-step explanation:
Part 1) we have
[tex]f(x)=\frac{2x-1}{x+2}[/tex]
Find the inverse
Let
y=f(x)
[tex]y=\frac{2x-1}{x+2}[/tex]
Exchange the variables x for y and t for x
[tex]x=\frac{2y-1}{y+2}[/tex]
Isolate the variable y
[tex]x=\frac{2y-1}{y+2}\\ \\ xy+2x=2y-1\\ \\xy-2y=-2x-1\\ \\y[x-2]=-2x-1\\ \\y=\frac{-2x-1}{x-2}[/tex]
Let
[tex]f^{-1}(x)=y[/tex]
[tex]f^{-1}(x)=\frac{-2x-1}{x-2}[/tex]
Part 2) we have
[tex]f(x)=\frac{x-1}{2x+1}[/tex]
Find the inverse
Let
y=f(x)
[tex]y=\frac{x-1}{2x+1}[/tex]
Exchange the variables x for y and t for x
[tex]x=\frac{y-1}{2y+1}[/tex]
Isolate the variable y
[tex]x=\frac{y-1}{2y+1}\\ \\2xy+x=y-1\\ \\2xy-y=-x-1\\ \\y[2x-1]=-x-1\\ \\y=\frac{-x-1}{2x-1}[/tex]
Let
[tex]f^{-1}(x)=y[/tex]
[tex]f^{-1}(x)=\frac{-x-1}{2x-1}[/tex]
Part 3) we have
[tex]f(x)=\frac{2x+1}{2x-1}[/tex]
Find the inverse
Let
y=f(x)
[tex]y=\frac{2x+1}{2x-1}[/tex]
Exchange the variables x for y and t for x
[tex]x=\frac{2y+1}{2y-1}[/tex]
Isolate the variable y
[tex]x=\frac{2y+1}{2y-1}\\ \\2xy-x=2y+1\\ \\2xy-2y=x+1\\ \\y[2x-2]=x+1\\ \\y=\frac{x+1}{2(x-1)}[/tex]
Let
[tex]f^{-1}(x)=y[/tex]
[tex]f^{-1}(x)=\frac{x+1}{2(x-1)}[/tex]
Part 4) we have
[tex]f(x)=\frac{x+2}{-2x+1}[/tex]
Find the inverse
Let
y=f(x)
[tex]y=\frac{x+2}{-2x+1}[/tex]
Exchange the variables x for y and t for x
[tex]x=\frac{y+2}{-2y+1}[/tex]
Isolate the variable y
[tex]x=\frac{y+2}{-2y+1}\\ \\-2xy+x=y+2\\ \\-2xy-y=-x+2\\ \\y[-2x-1]=-x+2\\ \\y=\frac{-x+2}{-2x-1} \\ \\y=\frac{x-2}{2x+1}[/tex]
Let
[tex]f^{-1}(x)=y[/tex]
[tex]f^{-1}(x)=\frac{x-2}{2x+1}[/tex]
Part 5) we have
[tex]f(x)=\frac{x+2}{x-1}[/tex]
Find the inverse
Let
y=f(x)
[tex]y=\frac{x+2}{x-1}[/tex]
Exchange the variables x for y and t for x
[tex]x=\frac{y+2}{y-1}[/tex]
Isolate the variable y
[tex]x=\frac{y+2}{y-1}\\ \\xy-x=y+2\\ \\xy-y=x+2\\ \\y[x-1]=x+2\\ \\y=\frac{x+2}{x-1}[/tex]
Let
[tex]f^{-1}(x)=y[/tex]
[tex]f^{-1}(x)=\frac{x+2}{x-1}[/tex]
Answer:
Step-by-step explanation:
How many solutions does the equation 5x + 3x − 4 = 10 have? Zero One Two Infinitely many
[tex]5x + 3x -4 = 10\\8x=14\\x=\dfrac{14}{8}=\dfrac{7}{4}[/tex]
one
Answer:0ne
Step-by-step explanation:
Can you use the ASA Postulate or the AAS Theorem to prove the triangles congruent? (1)
Answer:
asa only because the two triangles are facing each other like a reflection making them congruent
ΔWZV and ΔWZY are congruent by AAS congruency
What is congruency?Congruent triangles are triangles having both the same shape and the same size.Types of congruencies are SSS, SAS, AAS, ASA, RHS.How to prove that the triangles are congruent?In the given figure there are two triangles, ΔWZV and ΔWZYConsidering ΔWZV and ΔWZY
∠WVZ = ∠WYZ (given)
∠WZV = ∠WZY ( both angles are 90° since it is given that WZ is perpendicular to VY)
WZ is common side
So ΔWZV and ΔWZY are congruent (AAS congruency)
Find more about "Congruency" here: https://brainly.com/question/2938476
#SPJ2
What is the order of rotational symmetry for the figure
Answer:
B. 3
Step-by-step explanation:
First of all we will define rotational symmetry.
Rotational symmetry is when a shape looks the same after some rotation or less than one rotation.
The order of rotational symmetry is how many times it matches the original shape during the rotation.
So, for the given shape the rotated shape will match the original shape three times so the order for symmetry for the given shape is 3.
Hence,
the correct answer is B. 3 ..
What is the angle of elevation of the sun if a 45 foot tall flagpole casts a 22 foot long shadow?
Answer:
the angle Ф is 63.9 degrees.
Step-by-step explanation:
A right triangle describes this situation. The height of the triangle is 45 ft and the base is 22 ft. The ratio height / base is the tangent of the angle of elevation and is tan Ф. We want to find the angle Ф:
opp
tan Ф = ---------- = 45 / 22 = 2.045.
adj
Using the inverse tangent function on a calculator, we find that the angle Ф is 63.9 degrees.
please help anyone.
Answer:
- [tex]\frac{27}{7}[/tex]
Step-by-step explanation:
Given
f(x) = [tex]\frac{3}{x+2}[/tex] - [tex]\sqrt{x-3}[/tex]
Evaluate f(19) by substituting x = 19 into f(x)
f(19) = [tex]\frac{3}{19+2}[/tex] - [tex]\sqrt{19-3}[/tex]
= [tex]\frac{3}{21}[/tex] - [tex]\sqrt{16}[/tex]
= [tex]\frac{1}{7}[/tex] - 4
= [tex]\frac{1}{7}[/tex] - [tex]\frac{28}{7}[/tex] = - [tex]\frac{27}{7}[/tex]
Find the sum (4s/ s2-2s+1)+(7/s2+2s-3)
Answer:
It would be 7/2s, however if you want to solve it completely, you do 7 ÷ 2. It would give you 3.5 so, s = 3.5.
(05.03)Marcus loves baseball and wants to create a home plate for his house. Marcus needs to calculate the area of the home plate at the ball field so he can reconstruct it when he gets home. Calculate the area of the polygon. Pentagon with square measuring 8 inches by 5 inches and two triangles with heights of 7 inches and 6 inches.
72.5 in2
75.5 in2
83 in2
96 in2
Answer:
83 square inches
Step-by-step explanation:
Let's find the answer, you can see the attached file for clarity.
Because we have a rectangle measuring 8 inches by 5 inches, we can use the area of the rectangle as follows:
A1=base*height=(8 inches)*(5 inches)=40 square inches
Now, because we have a triangle over the square side of 8 inches long, we can divide the triangle into 2 rectangle triangles, each of them with a base of 4 inches and a height of 7 inches, obtaining:
A2=2*(base*height/2)=2*(4 inches)*(7 inches)/2=28 square inches
Doing the same for the other triangle we get 2 triangles with a base of 2.5 inches and a height of 6 inches, obtaining:
A3=2*(base*height/2)=2*(2.5 inches)*(6 inches)/2=15 square inches
The addition of all areas is:
A=A1+A2+A3=40 square inches + 28 square inches + 15 square inches
A=83 square inches.
In conclusion we have an area of 83 square inches.
Answer:
83
Step-by-step explanation:
Find the slope between (3, 2) and (-2, 3)
For this case we have that by definition, the slope of a line is given by:
[tex]m = \frac {y_ {2} -y_ {1}} {x_ {2} -x_ {1}}[/tex]
We have the following points:
[tex](x_ {1}, y_ {1}) :( 3,2)\\(x_ {2}, y_ {2}): (- 2,3)[/tex]
Substituting we have:
[tex]m = \frac {3-2} {- 2-3} = \frac {1} {- 5} = - \frac {1} {5}[/tex]
Finally, the slope is:
[tex]m = - \frac {1} {5}[/tex]
Answer:
[tex]m = - \frac {1} {5}[/tex]
Jenny and Hanan are collecting clothes for a clothing drive. Hanan collected 1/2 as many bags of clothes as Jenny did. If Jenny collected 3/ 4 of a bag of clothes, what portion of a bag of clothes did Hanan collect?
Answer:
Hanan collect [tex]\frac{3}{8}[/tex] of a bag of clothes
Step-by-step explanation:
Let
x ------> amount of clothing bag that Jenny collected
y ------> amount of clothing bag that Hanan collected
we know that
[tex]y=\frac{1}{2}x[/tex] -----> equation A
[tex]x=\frac{3}{4}[/tex] -----> equation B
Substitute equation B in equation A
[tex]y=\frac{1}{2}(\frac{3}{4})[/tex]
[tex]y=\frac{3}{8}[/tex]
therefore
Hanan collect [tex]\frac{3}{8}[/tex] of a bag of clothes
what is the length of CD, given that figure ABCD is a rectangle
Answer:
where is rectangle???
Answer:
10
Step-by-step explanation:
The length of AB is 10 and the length of BC is 13. CD is parallel to AB so its 10.
(4 - 7n) – (20+5)
Simplify expression
(4 - 7n) – (20+5)
Simplify:
(4 -7n) - 25
Remove parenthesis:
4 - 7n -25
Combine like terms:
4-25 = -21
Now you have: -21-7n
The term with the variable is usually rearranged to be in front, so it becomes: -7n-21